Type-2-low severe asthma endotypes for new treatments: the new asthma frontier. Issue 3 (12th June 2023) - Chung, Kian Fan
Abstract : Purpose of review: Type-2 (T2)-high asthma represents a well defined group of severe eosinophilic asthma for which there are now effective biologic therapies targetting the interleukins (ILs) 4, 5 and 13, and Immunoglobulin E. T2-low asthma detected in the clinic by a low blood eosinophil count remains ill-defined and is the focus of this review. Recent findings: By analysing transcriptomic and proteomic expression in sputum samples in U-BIOPRED cohort, both T2-high and -low molecular phenotypes have been described. Using clustering approaches, a neutrophilic-predominant cluster associated with activation markers of neutrophilic and inflammasome activation with interferon and tumour necrosis factor expression, together with a cluster of paucigranulocytic inflammation linked to oxidative phosphorylation and senescence pathways have been described. Using gene set variation analysis, specific molecular phenotypes driven by IL-6 trans-signalling pathway, or those by IL-6, IL-17 and IL-22 pathways were identified linked to a mixed granulocytic or neutrophilic inflammation. Summary: Previous trials of antineutrophilic agents in asthma have failed because enrolled patients were not specifically chosen for these targeted treatments. Although the T2-low molecular pathways should be validated in other cohorts, the availability of targeted therapies indicated for other autoimmune conditions should encourage a trial of these respective biological therapies for these specific molecular phenotypes.